Persepsi, Pengetahuan, Dan Kesadaran Tentang Kesehatan Pranikah Terhadap Sikap Pemeriksaan Kesehatan Pranikah - Dian Purnama Sari; Dyah Triwidiyantari; Sheli Riani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
The attitude of the bride and groom is a form of active community participation in premarital health checks. The bride and groom are expected to be able to carry out activities in order to improve health status because. This study aims to assess the relationship between perceptions, knowledge, and awareness, about premarital health with premarital examination attitudes. The research design used is Crosssectional. Collecting data using a questionnaire that is served and analyzed using Multiple Regression. The sampling method used is probability sampling. The data quality test used is a validity test using Corrected Item Total and a reliability test using Cronbach Alpha. To test the hypothesis in this study, the researcher used F test. The results of this study indicate that the variables of perception, and awareness have an influence on premarital examination..